2006
DOI: 10.1161/circulationaha.105.000562
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hemoglobin Vesicles During Cardiopulmonary Bypass Priming Prevents Neurocognitive Decline in Rats

Abstract: Background— Homologous blood use is considered to be the gold standard for cardiopulmonary bypass (CPB) priming in infants despite exposure of the patient to potential cellular and humoral antigens. However, the use of hemoglobin vesicles (HbVs), artificial oxygen carriers that encapsulate a concentrated hemoglobin solution within phospholipid bilayer membranes, for CPB priming may prevent neurocognitive decline in infants. The goal of this study was to determine whether HbV use offset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
(24 reference statements)
1
27
0
Order By: Relevance
“…Addition of a plasma substitute solution such as recombinant albumin is effective to regulate colloid osmotic pressure Sakai et al, 2004;. We confirmed sufficient O 2 -transport comparable with RBC in the animal experiments of extreme hemodilution up to 90% blood exchange and resuscitation from hemorrhagic shock, and priming solution for cardiopulmonary bypass (ECMO) (Yamazaki et al, 2006).…”
Section: Hemoglobin-vesiclessupporting
confidence: 58%
“…Addition of a plasma substitute solution such as recombinant albumin is effective to regulate colloid osmotic pressure Sakai et al, 2004;. We confirmed sufficient O 2 -transport comparable with RBC in the animal experiments of extreme hemodilution up to 90% blood exchange and resuscitation from hemorrhagic shock, and priming solution for cardiopulmonary bypass (ECMO) (Yamazaki et al, 2006).…”
Section: Hemoglobin-vesiclessupporting
confidence: 58%
“…Previous reports (11,30) indicated that neurocognitive dysfunction could be produced by cardiopulmonary bypass which also involves II/R. In addition, the survivors who suffered from critical diseases involving systemic inflammatory response were commonly left with long-term cognitive dysfunction and impairment of life quality (31).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacodynamic, serologic, or metabolic analysis of the reticuloendothelial system has also been performed, [1012] as have preclinical studies of the long-term survival of dogs after exchange transfusion of HbV. [13] While HbVs have been used to prime the fluid of heart-lung machines,[14] their perioperative effects have not been evaluated. In this study, we examined the performance of HbVs in a mouse model of pneumonectomy by monitoring postoperative survival and recovery.…”
Section: Introductionmentioning
confidence: 99%